INTERACTIVE METHODS OF TEACHING ENGLISH ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2023)
The article discusses interactive methods of teaching English. The author describes the possibility of using some of these methods and techniques in an English lesson.